Methylmalonic Acidemia with Novel MUT Gene Mutations - Inusha Panigrahi; Savita Bhunwal; Harish Varma; Simranjeet Singh (Case Reports in Genetics)
A 5-year-old boy presented with recurrent episodes of fever, feeding problems, lethargy, from the age of 11 months, and poor weight gain. He was admitted and evaluated for metabolic causes and diagnosed as having methylmalonic acidemia (MMA). He was treated with vit B12 and carnitine supplements and has been on follow-up for the last 3 years. Mutation analysis by next generation sequencing (NGS), supplemented with Sanger sequencing, revealed two novel variants in the MUT gene responsible for MMA in exon 5 and exon 3, respectively. Recently he developed dystonic movements including orofacial dyskinesia. With advent of NGS, judicious use of NGS with Sanger sequencing can help identify causative possibly pathogenic mutations.